A sunscreen composition, method of making and sunscreen product
Patent Information
- Application Number
- CN202611223267.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
但是,这种无机防晒霜在涂抹于皮肤时可能会引发白浊现象等,附着力下降,在确保长时间持续的防晒效果方面存在局限性
本发明创新地提供了一种新的防晒组合物,该防晒组合物在具备较优异的防晒能力基础上能够兼具较好的贴肤性能、剂型稳定性等,改善甚至克服了目前防晒产品存在的难以兼顾防晒性能和使用感平衡以及稳定性等问题。
Smart Images

Figure CN122997992A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of daily chemical products, specifically to a sunscreen composition, its preparation method, and sunscreen products. Background Technology
[0002] With increased outdoor activities and changing climate, the intensity and frequency of ultraviolet (UV) exposure to the skin are trending upwards. Consequently, the demand for cosmetics that prevent UV damage and pigmentation continues to grow. In particular, there is a need to develop sunscreens that can be used for extended periods in daily life, offering high SPF, minimal skin irritation, and excellent stability.
[0003] Another challenge in developing sunscreen products is balancing sun protection performance with user experience. Currently, most permitted sunscreen agents are oil-soluble, with only phenylbenzimidazole sulfonic acid (PBSA), terephthalic dicamphor sulfonic acid and its salts (TDSA and its salt), and disodium phenyl dibenzimidazole tetrasulfonate (DPDBT) being water-soluble. However, these are mostly acidic ingredients, requiring neutralization with alkalis, which may cause reactions in some sensitive skin types. Furthermore, these water-based sunscreens tend to create a sticky feel when used in formulations, increasing the difficulty of developing a lightweight, non-greasy feel. Based on these requirements, using inorganic sunscreen agents with excellent photostability to ensure high barrier properties is another approach. However, such inorganic sunscreens may cause whitening or decreased adhesion when applied to the skin, limiting their ability to ensure long-lasting sun protection. Summary of the Invention
[0004] The purpose of this invention is to overcome one or more deficiencies in the prior art and provide a new sunscreen composition that can solve at least one problem in the prior art.
[0005] The present invention also provides a method for preparing the above-mentioned sunscreen composition and its application in the preparation of sunscreen products.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A sunscreen composition, wherein the ingredients of the sunscreen composition comprise: The oil phase contains at least one emulsifier; the amount of the emulsifier added is 0.8 wt.%-5.5 wt.% based on the total weight of the sunscreen composition; the emulsifier comprises one or more combinations selected from arachidonic acid / behenol / arachidonic acid glucoside, cetearyl oleate / sorbitan oleate, cetearyl alcohol, C20-22 phosphate ester / C20-22 alcohol; The sunscreen composition includes an aqueous phase containing at least a thickener; the thickener comprises at least a combination of polyacrylate crosspolymer-6 and xanthan gum, wherein the amount of xanthan gum added is 0.03 wt.%-0.25 wt.% and the amount of polyacrylate crosspolymer-6 added is 0.06 wt.%-0.35 wt.% based on the total weight of the sunscreen composition. Inorganic sunscreen agent; the amount of inorganic sunscreen agent added is 0.5 wt.%-5.0 wt.% based on the total weight of the sunscreen composition; and the inorganic sunscreen agent exists as a single phase or is pre-dispersed in the oil phase and / or the aqueous phase.
[0007] In some embodiments of the present invention, the amount of emulsifier added is 1.0 wt.%-5.0 wt.%, more specifically 2.5 wt.%-4.0 wt.%, based on the total weight of the sunscreen composition.
[0008] According to some specific aspects of the present invention, the amount of emulsifier added, based on the total weight of the sunscreen composition, is 1.0 wt.%, 1.2 wt.%, 1.5 wt.%, 1.8 wt.%, 2.0 wt.%, 2.2 wt.%, 2.5 wt.%, 2.8 wt.%, 3.0 wt.%, 3.2 wt.%, 3.5 wt.%, 3.8 wt.%, 4.0 wt.%, 4.2 wt.%, 4.5 wt.%, 4.8 wt.%, 5.0 wt.%, etc.
[0009] In some embodiments of the present invention, the amount of xanthan gum added is 0.04 wt.%-0.22 wt.% based on the total weight of the sunscreen composition, and the amount of polyacrylate crosspolymer-6 added is 0.08 wt.%-0.32 wt.%.
[0010] Furthermore, based on the total weight of the sunscreen composition, the amount of xanthan gum added is 0.05 wt.%-0.20 wt.%, and the amount of polyacrylate crosspolymer-6 added is 0.1 wt.%-0.3 wt.%.
[0011] Furthermore, based on the total weight of the sunscreen composition, the amount of xanthan gum added is 0.05 wt.%-0.15 wt.%, and the amount of polyacrylate crosspolymer-6 added is 0.1 wt.%-0.20 wt.%.
[0012] According to some specific aspects of the present invention, the amount of xanthan gum added, based on the total weight of the sunscreen composition, is 0.04 wt.%, 0.05 wt.%, 0.06 wt.%, 0.08 wt.%, 0.09 wt.%, 0.1 wt.%, 0.11 wt.%, 0.12 wt.%, 0.13 wt.%, 0.15 wt.%, 0.16 wt.%, 0.18 wt.%, 0.20 wt.%, 0.21 wt.%, 0.22 wt.%, 0.23 wt.%, 0.25 wt.%, etc.
[0013] According to some specific aspects of the present invention, based on the total weight of the sunscreen composition, the amount of the polyacrylate crosspolymer-6 added is 0.06 wt.%, 0.08 wt.%, 0.10 wt.%, 0.12 wt.%, 0.13 wt.%, 0.14 wt.%, 0.15 wt.%, 0.16 wt.%, 0.17 wt.%, 0.18 wt.%, 0.19 wt.%, 0.20 wt.%, 0.21 wt.%, 0.22 wt.%, 0.23 wt.%, 0.24 wt.%, 0.25 wt.%, 0.26 wt.%, 0.27 wt.%, 0.28 wt.%, 0.29 wt.%, 0.30 wt.%, 0.32 wt.%, 0.33 wt.%, 0.34 wt.%, 0.35 wt.%, etc.
[0014] In some embodiments of the present invention, the amount of inorganic sunscreen agent added is 2wt.%-4wt.% based on the total weight of the sunscreen composition.
[0015] According to some specific aspects of the present invention, the amount of the inorganic sunscreen agent added, based on the total weight of the sunscreen composition, is 0.5 wt.%, 0.8 wt.%, 1.0 wt.%, 1.2 wt.%, 1.5 wt.%, 1.8 wt.%, 1.9 wt.%, 2.0 wt.%, 2.2 wt.%, 2.3 wt.%, 2.5 wt.%, 2.8 wt.%, 3.0 wt.%, 3.2 wt.%, 3.5 wt.%, 3.8 wt.%, 4.0 wt.%, 4.2 wt.%, 4.5 wt.%, 4.8 wt.%, 5.0 wt.%, etc.
[0016] In some embodiments of the present invention, the mass ratio of the polyacrylate crosslinked polymer-6 to the xanthan gum is 1:0.3-1.25, more specifically 1:0.35-1.0, and even more specifically 1:0.5-0.8.
[0017] According to some specific aspects of the present invention, the mass ratio of the polyacrylate crosslinked polymer-6 to the xanthan gum is 1:0.3, 1:0.32, 1:0.35, 1:0.38, 1:0.39, 1:0.4, 1:0.42, 1:0.45, 1:0.48, 1:0.5, 1:0.52, 1:0.55, 1:0.58, 1:0.6, 1:0.62, 1∶0.65, 1∶0.66, 1∶0.68, 1∶0.7, 1∶0.72, 1∶0.75, 1∶0.78, 1∶0.8, 1∶0.82, 1∶0.85, 1∶0.88, 1∶0.9, 1∶0.92, 1∶0.95, 1∶0.98, 1∶1.0, 1∶1.05, 1∶1.08, 1∶1.1, 1∶1.2, 1∶1.22, etc.
[0018] In some embodiments of the present invention, the mass ratio of the emulsifier, the thickener and the inorganic sunscreen agent is 0.8-1.2:0.04-0.12:1.
[0019] According to some specific aspects of the present invention, the mass ratio of the emulsifier, the thickener, and the inorganic sunscreen agent is 0.8-1.2∶0.04-0.12∶1. The numerical range "0.8-1.2" can be 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1.0, 1.02, 1.05, 1.08, 1.1, 1.12, 1.15, 1.18, 1.2, etc., and the numerical range "0.04-0.12" can be 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, etc.
[0020] In some embodiments of the present invention, the inorganic sunscreen agent is a modified inorganic sunscreen agent, which includes a core layer and a shell layer. The core layer is made of inorganic sunscreen particles, and the shell layer is made of silicon dioxide and hydrogenated lecithin.
[0021] Furthermore, by mass percentage, the modified inorganic sunscreen agent comprises 75%-88% inorganic sunscreen particles, 10%-20% silica, and 0.01%-10% hydrogenated lecithin.
[0022] Furthermore, by mass percentage, the modified inorganic sunscreen agent comprises 80%-86% inorganic sunscreen particles, 12%-18% silica, and 0.5%-4% hydrogenated lecithin.
[0023] In some embodiments of the present invention, the inorganic sunscreen particles comprise titanium dioxide.
[0024] In some embodiments of the present invention, the inorganic sunscreen particles in the modified inorganic sunscreen agent account for 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88% by mass percentage.
[0025] In some embodiments of the present invention, the modified inorganic sunscreen agent contains silica in the following percentages by mass: 10%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20%, etc.
[0026] In some embodiments of the present invention, the modified inorganic sunscreen agent contains, by weight percentage, hydrogenated lecithin in the following proportions: 0.01%, 0.02%, 0.05%, 0.06%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1%. 0.0%, 1.2%, 1.5%, 1.6%, 1.8%, 1.9%, 2.0%, 2.2%, 2.3%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%, 5.2%, 5.5%, 5.8%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.2%, 7.5%, 7.8%, 8.0%, 8.2%, 8.5%, 8.8%, 9.0%, 9.5%, 9.8%, etc.
[0027] In some embodiments of the present invention, the modified inorganic sunscreen agent is prepared by the following method: (1) An aqueous solution of inorganic sunscreen particles was used as the substrate solution; (2) Under heating and stirring conditions, an aqueous solution of acid is added to the substrate solution to control the pH of the system to 3-5. Then, under heating and stirring conditions, an aqueous solution of sodium silicate and an aqueous solution of acid are added and the reaction is controlled at pH 3-4. After the reaction, the reaction mixture is obtained, separated, and inorganic sunscreen particles coated with silica are obtained. (3) The silica-coated inorganic sunscreen particles are activated under heating conditions and then mixed with hydrogenated lecithin.
[0028] In some embodiments of the present invention, during the preparation process, the aqueous solution of inorganic sunscreen particles is first mechanically ground and ultrasonically dispersed, and then heated.
[0029] According to the present invention, when the selected inorganic sunscreen particles, such as titanium dioxide, are commercially available, if the surface is untreated, a relatively dense coating layer is generally formed first to avoid damage to the skin caused by free radicals generated by titanium dioxide catalysis. In some embodiments of the present invention, the preparation method of the modified inorganic sunscreen agent further includes a pretreatment step set between step (2) and step (1). The pretreatment step includes: adding an aqueous solution of sodium silicate and an aqueous solution of acid to the substrate solution under heating and stirring conditions, reacting under conditions where the pH of the system is controlled at 8-9, and obtaining a pretreated reaction mixture after the reaction. If the commercially available inorganic sunscreen particles, such as titanium dioxide, have already been pre-modified, the above pretreatment step can be omitted.
[0030] In some embodiments of the present invention, during the preparation process, the content of silicon dioxide in the sodium silicate aqueous solution is controlled to be 40-60 g / L.
[0031] In some embodiments of the present invention, the aqueous solution of the acid includes one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.
[0032] In some embodiments of the present invention, during the process of obtaining the pretreated reaction mixture and the reaction mixture, the heating conditions are controlled to keep the system temperature at 50-60°C.
[0033] In some embodiments of the present invention, the activation is controlled to be carried out at 75-90°C, and further at 80-85°C.
[0034] In some embodiments of the present invention, the activated silica-coated inorganic sunscreen particles are mixed with hydrogenated lecithin at 75-90°C.
[0035] In some embodiments of the present invention, the mass of sodium silicate added is measured in terms of the amount of silicon dioxide. In the process of obtaining the pretreated reaction mixture or the reaction mixture, the mass of silicon dioxide added is 10%-40% of the mass of the inorganic sunscreen particles.
[0036] In some embodiments of the present invention, the amount of hydrogenated lecithin added is based on the principle that the amount of hydrogenated lecithin is 0.01%-10% of the modified inorganic sunscreen.
[0037] In some embodiments of the present invention, after adding hydrogenated lecithin and mixing, heat treatment is continued at 75-90°C, followed by pulverization.
[0038] In some embodiments of the present invention, titanium dioxide particles are used as an example of inorganic sunscreen particles for illustration. The method for preparing the modified inorganic sunscreen agent includes: A titanium dioxide aqueous solution (formed by dispersing titanium dioxide particles in water) was taken, and then mechanically ground and ultrasonically dispersed evenly. During the strong stirring and dispersion process, the reaction temperature was controlled at 50~60℃, and hydrochloric acid was slowly added. The pH of the reaction system was adjusted in real time to stabilize at 3~5. Subsequently, sodium silicate aqueous solution and hydrochloric acid were added again to adjust the pH of the reaction system to 3~4, and the reaction continued. After the reaction was completed, the mixture was washed multiple times with deionized water to remove soluble salts. After drying, a dry powder was obtained, which was then pulverized by air jet milling to obtain silica-coated titanium dioxide. The silica-coated titanium dioxide prepared according to the above method was added to a mixer and heated to 80-85°C to activate the surface. Hydrogenated lecithin was prepared into a solution, uniformly atomized, and sprayed into the mixer at a constant speed. Mixing was continued at 80-85°C. After mixing, the mixture was cooled to room temperature. The coated material was transferred to a tray and then heat-treated at 80-85°C. Finally, it was subjected to air jet milling to obtain the modified inorganic sunscreen agent.
[0039] In some embodiments of the present invention, titanium dioxide particles are used as an example of inorganic sunscreen particles for illustration. The method for preparing the modified inorganic sunscreen agent includes: A titanium dioxide aqueous solution (formed by dispersing titanium dioxide particles in water) was prepared and uniformly dispersed by mechanical grinding and ultrasonication. During vigorous stirring and dispersion, the reaction temperature was controlled at 50-60℃, while sodium silicate aqueous solution and hydrochloric acid were slowly added. The pH of the reaction system was adjusted in real time to stabilize it at 8-9, allowing sodium silicate to hydrolyze to form hydrated silica, which gradually deposited on the surface of the titanium dioxide particles to form a dense silica coating layer. Subsequently, the pH of the reaction system was adjusted to 3-5, and the temperature was maintained at 50-60℃ under vigorous stirring. Sodium silicate aqueous solution and hydrochloric acid were added again, and the pH was controlled to stabilize it at 3-4, allowing sodium silicate to hydrolyze to form silicic acid, which gradually deposited to form a loose silica coating layer. After the reaction was completed, the mixture was washed multiple times with deionized water to remove soluble salts; dried to obtain a dry powder, which was then pulverized by air jet milling to obtain silica-coated titanium dioxide. The silica-coated titanium dioxide prepared according to the above method is added to a mixer and heated to 80-85°C to activate the surface. Hydrogenated lecithin is uniformly atomized and sprayed into the mixer at a constant speed, and mixing continues at 80-85°C. After mixing, the mixture is cooled to room temperature, and the coated material is transferred to a tray for heat treatment at 80-85°C. Finally, it is subjected to air jet milling to obtain the modified inorganic sunscreen agent.
[0040] In some embodiments of the present invention, the oil phase further comprises an oil-soluble sunscreen ingredient.
[0041] In some embodiments of the present invention, the oil-soluble sunscreen ingredient comprises one or more combinations selected from homosalate, octocrylene, ethylhexyl salicylate, ethylhexyl methoxyate, and diethylamino hydroxybenzoyl hexyl benzoate.
[0042] Furthermore, based on the total weight of the sunscreen composition, the amount of homosalate added is 1 wt.%-5 wt.%, the amount of octocrylene added is 0.5 wt.%-4.5 wt.%, the amount of ethylhexyl salicylate added is 2.5 wt.%-6.5 wt.%, the amount of ethylhexyl methoxyate added is 4.5 wt.%-9.0 wt.%, and the amount of diethylamino hydroxybenzoyl hexyl benzoate added is 1 wt.%-5 wt.%.
[0043] According to certain aspects of the present invention, based on the total weight of the sunscreen composition, the amount of homosalate added is 2 wt.%-4 wt.%, the amount of octocrylene added is 1.5 wt.%-3.5 wt.%, the amount of ethylhexyl salicylate added is 3.5 wt.%-5.5 wt.%, the amount of ethylhexyl methoxyate added is 6.0 wt.%-8.0 wt.%, and the amount of diethylamino hydroxybenzoyl hexyl benzoate added is 2 wt.%-4 wt.%.
[0044] In some embodiments of the present invention, the aqueous phase further comprises polyols and skin feel modifiers.
[0045] Furthermore, based on the total weight of the sunscreen composition, the amount of the polyol added is 5 wt.%-15 wt.%, and the amount of the skin feel modifier added is 0.5 wt.%-3 wt.%.
[0046] In some embodiments of the present invention, the polyol may include, but is not limited to, butanediol, tromethamine, etc.
[0047] Furthermore, based on the total weight of the sunscreen composition, the amount of butylene glycol added is 4 wt.%-12 wt.%, and the amount of tromethamine added is 0.1 wt.%-0.8 wt.%.
[0048] According to some specific aspects of the invention, based on the total weight of the sunscreen composition, the amount of butylene glycol added is 5 wt.%-10 wt.%, and the amount of tromethamine added is 0.1 wt.%-0.5 wt.%.
[0049] In some embodiments of the present invention, the skin feel modifier may include, but is not limited to, silica, etc.
[0050] In some embodiments of the present invention, the raw materials of the sunscreen composition further include a preservative, and further, based on the total weight of the sunscreen composition, the amount of the preservative added is 0.1 wt.%-3 wt.%.
[0051] In some embodiments of the present invention, the preservative comprises one or more combinations selected from 1,2-hexanediol, ethylhexylglycerin, and glyceryl caprylate.
[0052] In some embodiments of the present invention, based on the total weight of the sunscreen composition, the amount of 1,2-hexanediol added is 0.5 wt.%-4 wt.%, the amount of ethylhexylglycerin added is 0.01 wt.%-0.3 wt.%, and the amount of glyceryl caprylate added is 0.01 wt.%-0.3 wt.%.
[0053] Further, based on the total weight of the sunscreen composition, the amount of 1,2-hexanediol added is 1 wt.%-3 wt.%, the amount of ethylhexylglycerin added is 0.05 wt.%-0.2 wt.%, and the amount of glyceryl caprylate added is 0.05 wt.%-0.2 wt.%.
[0054] According to some specific aspects of the invention, the sunscreen composition is in the form of a cream.
[0055] Another technical solution provided by the present invention: a method for preparing the sunscreen composition described above, the preparation method comprising: The components of the aqueous phase are mixed to form an aqueous phase; The components of the oil phase are mixed to form the oil phase; The oil phase is added to the aqueous phase and emulsified. Then, the inorganic sunscreen agent is added and dispersed and mixed.
[0056] In some embodiments of the present invention, before adding the oil phase to the aqueous phase, the oil phase and the aqueous phase are heated to 70-90°C and further heated to 75-85°C.
[0057] In some embodiments of the present invention, the system temperature is controlled at 40-55°C before the inorganic sunscreen agent is added.
[0058] In some embodiments of the present invention, after adding the inorganic sunscreen agent, a preservative is added, the mixture is stirred, cooled, and defoamed.
[0059] Another technical solution provided by the present invention is a sunscreen product, wherein the sunscreen product comprises the sunscreen composition described above.
[0060] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: This invention innovatively provides a new sunscreen composition that, while possessing excellent sun protection capabilities, also exhibits good skin adhesion and formulation stability, thereby improving or even overcoming the current problems in sunscreen products that make it difficult to balance sun protection performance with user experience and stability. Attached Figure Description
[0061] Figure 1 This is a scanning electron microscope image of the modified inorganic sunscreen agent prepared in Example 1 of the present invention; Figure 2 The chart shows the SPF values and SPF growth rate of the sunscreen compositions obtained in Examples 1-5 and Comparative Examples 1-4 of this invention. Figure 3 These are the appearance diagrams of the sunscreen compositions obtained in Comparative Examples 1-4, Example 1, and Examples 4-5 of the present invention; Figure 4 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 13 of the present invention; Figure 5 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 14 of the present invention; Figure 6 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 15 of the present invention; Figure 7 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 16 of the present invention; Figure 8 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 17 of the present invention; Figure 9 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 18 of the present invention; Figure 10 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 19 of the present invention; Figure 11 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 5 of the present invention; Figure 12 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 6 of the present invention; Figure 13 This is a stability test diagram of the sunscreen composition obtained in Example 6 of the present invention; Figure 14 This is a stability test diagram of the sunscreen composition obtained in Example 7 of the present invention; Figure 15 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 7 of the present invention; Figure 16 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 8 of the present invention; Figure 17This is a stability test diagram of the sunscreen composition obtained in Comparative Example 9 of the present invention; Figure 18 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 10 of the present invention; Figure 19 This is a stability test diagram of the sunscreen composition obtained in Example 8 of the present invention; Figure 20 This is a stability test diagram of the sunscreen composition obtained in Example 9 of the present invention; Figure 21 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 11 of the present invention; Figure 22 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 12 of the present invention; Figure 23 This is a stability test diagram of the sunscreen composition obtained in Example 10 of the present invention; Figure 24 This is a stability test diagram of the sunscreen composition obtained in Example 11 of the present invention; Figure 25 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 20 of the present invention; Figure 26 This is a stability test diagram of the sunscreen composition obtained in Example 12 of the present invention; Figure 27 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 21 of the present invention; Figure 28 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 22 of the present invention; Figure 29 This is a stability test diagram of the sunscreen composition obtained in Example 13 of the present invention; Figure 30 This is a stability test diagram of the sunscreen composition obtained in Example 14 of the present invention; Figure 31 This is a stability test diagram of the sunscreen composition obtained in Comparative Example 23 of the present invention; Figure 32 This is a stability test diagram of the sunscreen composition obtained in Example 5 of the present invention. Detailed Implementation
[0062] The above-mentioned solution will be further described below with reference to specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0063] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.
[0064] Hydrogenated lecithin: purchased from NIPPON SURFACTANT INDUSTRIES, brand name NIKKOL LECINOL S-10; Titanium dioxide: purchased from Changzhou Nao New Materials Technology Co., Ltd., brand name NAOCOS BST918. Xanthan gum: purchased from TATE & LYLE, brand name KELTROL® F XANTHAN GUM; Carrageenan: purchased from TATE & LYLE, brand name GENUVISCO® carrageenan CG-131; Carbomer: purchased from LUBRIZOL, brand name CARBOPOL® 980 Polymer; Polyvinylpyrrolidone: purchased from ASHLAND INC., brand name PVP K-30 powder; Polyacrylate crosspolymer-6: purchased from SEPPICS.A., brand name SEPIMAX ZEN. Arachidyl alcohol / behenyl alcohol / arachidyl alcohol glucoside, purchased from SEPPIC, brand name MONTANOV 202; cetearyl alcohol oleate / sorbitan oleate, purchased from HALLSTAR, brand name OLIVEM 1000; PEG-100 stearate / glyceryl stearate, purchased from CRODA, brand name SP ARLACEL 165 FP MBAL-PA-(SG) (version _1.0); cetearyl alcohol, purchased from BASF, brand name LANETTE® O.
[0065] In the following cases, the performance evaluation methods include: (1) SPF value test Testing instrument: UV2000S; Test method: 1) After thoroughly shaking the sample, weigh 0.032g of sample and evenly spot it onto a PMMA plate. Then, using gloved fingers, spread it evenly on a 25cm plate. 2 1) Apply the sample to three PMMA plates. 2) Apply the sample to three plates using the same method. 3) Place the PMMA plates coated with the sample in the dark for 15 minutes. Test the SPF value using a UV2000S instrument: Zero the instrument with a blank plate. After the instrument is properly adjusted, select 5 points on each PMMA plate for testing. After testing all three plates, calculate the SPF value using software.
[0066] (2) Evaluation of user experience (including skin-fit) Testing Method: Consumer Testing. Ten eligible participants were selected. The sample was evenly applied to the clean inside of their arms, and sensory evaluations were conducted, scoring the sample on its hydration, ease of application, whitening, and skin adherence. Each item was scored from 0 to 5 points, with higher scores indicating greater acceptance or approval of the tested dimension. The scores from the ten participants were then averaged.
[0067] (3) Stability evaluation Testing instrument: DAIHAN Scientific Thermo Stable IS-20; Test principle: The machine has an internal platform with a mechanical control track at the bottom, which can precisely control the speed and frequency of the platform's shaking. The inner layer is a sealed space, which can precisely control the internal temperature, and can achieve high temperature + synchronous shaking conditions to accelerate the observation of the stability of the emulsion.
[0068] Test method: Fix the test sample on the sample stage, set the temperature to 40℃, set the shaking speed of the sample stage to 250 rpm, and the time to 1 hour; observe the state of the test sample.
[0069] (4) Physical property testing (viscosity test) Test instrument: AMETERBROOK FIELD LVT230; Test method: Select rotor No. 64, immerse the rotor in the material, take a reading after a fixed time of 1 minute, and calculate the viscosity value.
[0070] (5) Description of the sample's appearance: Differentiating the appearance of samples: ① Good emulsion state, no visible oil precipitation or water separation: OK; ② Poor emulsion state, slight oil droplets or oil bands visible: Slight oil leakage; ③ Poor emulsion state, obvious oil droplets or oil bands visible: Oil leakage; ④ Extremely poor emulsion state, large areas of oil and powder precipitation visible, oil and water separation: Severe oil leakage; ⑤ Uneven material dispersion, visible local accumulation or aggregation: Agglomeration.
[0071] Example 1: This example provides a sunscreen composition and its preparation method. The formulation of the sunscreen composition is shown in Table 1.
[0072] Table 1 The inorganic sunscreen agent in this example is a modified inorganic sunscreen agent, which is prepared by the following method: Take 1 L of titanium dioxide aqueous solution (titanium dioxide content approximately 90 g / L), and disperse it evenly through mechanical grinding and ultrasonication. During vigorous stirring and dispersion, control the reaction temperature at 55±5℃, and slowly add 10% hydrochloric acid. Adjust the pH of the reaction system in real time and stabilize it at around 4. Then, add 0.5 L of sodium silicate aqueous solution (silica content approximately 50 g / L) and 10% hydrochloric acid, and control the pH to stabilize at around 3.5. React for 4 hours. After the reaction, wash three times with deionized water to remove soluble salts; dry at 95±5℃ for 8 hours to obtain a dry powder, which is then pulverized by air jet milling to obtain silica-coated titanium dioxide.
[0073] 10 kg of silica-coated titanium dioxide prepared according to the above method was added to a mixer and heated and mixed at 82±5℃ for 3 h to activate the surface. Approximately 2% (w / w) of hydrogenated lecithin (dissolved in isododecane solvent to prepare a 20% mass concentration solution before atomization) was uniformly atomized and sprayed into the mixer at a constant speed. Mixing continued at 82±5℃ for 3 h. After mixing, the mixture was cooled to room temperature, and the coated material was transferred to a tray. It was then heat-treated at 82±5℃ for 3 h, and finally pulverized by air jet milling to obtain the modified inorganic sunscreen. Scanning electron microscopy was used to test the modified inorganic sunscreen obtained from the silica and hydrogenated lecithin surface-treated titanium dioxide. The results are as follows: Figure 1 As shown in the figure, the sunscreen agent after treatment is evenly distributed, and no obvious large particle agglomeration was observed.
[0074] Titanium dioxide content analysis Weigh an appropriate amount (0.05 g) of modified inorganic sunscreen agent or titanium dioxide BST918 sample into a digestion tube. Add 2.5 mL of sulfuric acid (98% by mass) and 2.5 mL of nitric acid (68% by mass) along the tube wall. Measure 1 mL of hydrofluoric acid using a disposable dropper and place it on an acid-removing plate. Digest at 140℃ for 120 min, then increase the temperature to 180℃ and digest for 60 min. Cool to room temperature and transfer the liquid from the digestion tube to a colorimetric tube. Dilute the sample 10 times again to obtain the test solution. Simultaneously, prepare a reagent blank using the same procedure. Filter the sample through a 0.45 μm microporous membrane. Measure the intensity values of the filtered sample and reagent blank using ICP-OES. Determine the mass concentration of titanium (Ti) in the test solution according to the standard curve. Calculate the titanium dioxide content in the sample using the following formula.
[0075] Formula: X = {(C - C0) × V / m} × N / 10000; In the formula: X: the content of titanium dioxide in the modified inorganic sunscreen, %; C: Mass concentration of titanium in the test solution, μg / mL; C0: Mass concentration of titanium in the blank solution, μg / mL; V: Total dilution volume, mL; m: Sample weight, g; N: Conversion factor (the conversion factor for titanium dioxide is 1.6681).
[0076] The test results are shown in Table 2.
[0077] Table 2 According to the results shown in Table 2, the actual content of titanium dioxide in both the modified inorganic sunscreen and titanium dioxide BST918 reached more than 98% of the theoretical content, and were very close with no significant difference.
[0078] The preparation method of the sunscreen composition in this example includes: weighing each component according to the formulation amount in Table 1, mixing component A, component B, and component C to form an aqueous phase; mixing each component in component D to form an oil phase; heating the aqueous phase and oil phase to 80°C in a constant temperature water bath, then adding the oil phase to the aqueous phase, emulsifying at 6500 rpm for 10 min, cooling to 50°C, then adding component E, dispersing at 5000 rpm for 5 min, and finally adding the pre-dispersed component F, dispersing at 5000 rpm for 2 min; cooling to room temperature and defoaming to obtain the sunscreen composition.
[0079] Example 2: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the inorganic sunscreen agent is replaced with an equal amount of a combination of titanium dioxide BST918 and hydrogenated lecithin, and the mass ratio of titanium dioxide BST918 to hydrogenated lecithin is 4.9:0.1.
[0080] Example 3: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the inorganic sunscreen agent is replaced with an equal mass of titanium dioxide BST918.
[0081] Example 4: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the amount of inorganic sunscreen agent added is adjusted to 0.5 wt.%, and water is used to make up to 100 wt.%.
[0082] Example 5: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the amount of inorganic sunscreen agent added is adjusted to 3 wt.%, and water is used to make up to 100 wt.%.
[0083] Comparative Example 1: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the inorganic sunscreen agent is added at a mass of 0 and water is used to make up to 100 wt.%.
[0084] Comparative Example 2: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the amount of inorganic sunscreen agent added is adjusted to 6 wt.%, and the amount of water added is reduced accordingly to keep the total amount at 100 wt.%.
[0085] Comparative Example 3: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the amount of inorganic sunscreen agent added is adjusted to 10 wt.%, and the amount of water added is reduced accordingly to keep the total amount at 100 wt.%.
[0086] Comparative Example 4: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 1, except that the amount of inorganic sunscreen agent added is adjusted to 0.05 wt.%, and water is used to make up to 100 wt.%.
[0087] Performance Test 1: (a) The SPF values of the sunscreen compositions obtained in Examples 1-5 and Comparative Examples 1-4 were tested, and the test results are shown in Table 3.
[0088] Table 3 From the above results, we can conclude that: Comparative Example 1 did not contain any inorganic sunscreen agents, while Comparative Example 4 contained inorganic sunscreen agents, but in very small amounts, resulting in a limited increase in SPF value. In Example 2, titanium dioxide BST918 was not modified and was only added simultaneously with hydrogenated lecithin; in Example 3, only titanium dioxide BST918 was added, and there was no significant difference in the SPF values between the two, indicating that simply adding hydrogenated lecithin physically has limited effect on improving SPF; however, it can be seen that Example 1 shows significant improvement compared to Examples 2-3, with an increase of about 18% or more, indicating that the modified inorganic sunscreen obtained according to the method of the present invention has a significant improvement effect on sun protection.
[0089] Although Comparative Examples 2-3 achieved good results in terms of SPF value, the excessive amount of modified inorganic sunscreen agent added would significantly increase production costs, which is not conducive to large-scale production.
[0090] The SPF values and SPF growth rate of the sunscreen compositions obtained in Examples 1-5 and Comparative Examples 1-4 (calculated as: (SPF value of Examples / Comparative Examples - SPF value of Comparative Example 1) / SPF value of Comparative Example 1 * 100%) are shown in the statistical chart. Figure 2 As shown in the figure, when the content of modified inorganic sunscreen agent gradually increases from 0.5% to 5%, the SPF value of the sunscreen increases significantly; while when the content of modified inorganic sunscreen agent increases from 5% to 10%, the SPF value of the sunscreen composition increases more slowly.
[0091] (II) User Experience Evaluation The user experience of the sunscreen compositions obtained in Examples 1-4, Example 1, and Examples 4-5 was compared. The test results are shown in Table 4. Figure 3 As shown.
[0092] Table 4 As the content of modified inorganic sunscreen agents increases, the state of the resulting sunscreen composition changes from a low-viscosity cream to a conventional cream, with decreased hydration, increased difficulty in application, and increased cloudiness. When the powder content exceeds 6%, the sunscreen composition becomes a paste, increasing application resistance and slowing absorption. Considering both sun protection effectiveness and user experience in the above tests, the optimal addition amount of modified inorganic sunscreen agents is greater than or equal to 0.5 wt.% and less than or equal to 5.0 wt.%, which can at least balance sun protection effectiveness and user experience.
[0093] Example 6: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, the amount of polyacrylate crosspolymer-6 added is adjusted to 0.1 wt.%, and the amount of xanthan gum added is adjusted to 0.1 wt.%; the amount of water added is adjusted accordingly to keep the total amount at 100 wt.%.
[0094] Example 7: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, the amount of polyacrylate crosspolymer-6 added is adjusted to 0.3 wt.% and the amount of xanthan gum added is adjusted to 0.1 wt.%; the amount of water added is adjusted accordingly to keep the total amount at 100 wt.%.
[0095] Example 8: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, the amount of polyacrylate crosslinking polymer-6 is maintained at 0.16 wt.%, and the amount of xanthan gum is adjusted to 0.05 wt.%. The amount of water added is adjusted accordingly to maintain the total at 100 wt.%.
[0096] Example 9: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, the amount of polyacrylate crosspolymer-6 is maintained at 0.16 wt.%, and the amount of xanthan gum is adjusted to 0.2 wt.%. The amount of water is adjusted accordingly to maintain the total at 100 wt.%.
[0097] Comparative Examples 5-12: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that the components and contents shown in Table 5 are used in component B.
[0098] Table 5 Performance Test 2: (a) The SPF value, adhesion, and stability of the sunscreen compositions obtained in Examples 6-9 and Comparative Examples 5-12 were tested. The test results are shown in Tables 6-7. Figures 11-22 , Figure 32 As shown.
[0099] Table 6 Table 7 1) According to Comparative Examples 5 and 12, when using xanthan gum as a single thickener, the stability of the prepared sunscreen was poor and the skin adhesion evaluation was low when the content ranged from 0.1 wt.% to 0.6 wt.%. According to Comparative Examples 8 and 9, when using polyacrylate crosspolymer-6 as a single thickener, the stability of the prepared sunscreen was poor and the skin adhesion evaluation was average when the content ranged from 0.16 wt.% to 0.6 wt.%. In summary, it is difficult to achieve stable stability of the prepared sunscreen composition when using both xanthan gum and polyacrylate crosspolymer-6. 2) As shown in Table 5, when the content of thickener xanthan gum is fixed at 0.1 wt.%, and the content of thickener polyacrylate crosspolymer-6 is increased from 0 wt.% to 0.5 wt.%, the SPF value of the prepared sunscreen composition shows a trend of first increasing and then decreasing; the skin adhesion evaluation also shows a trend of first increasing and then decreasing; when the content of thickener polyacrylate crosspolymer-6 is too low (<0.1 wt.%) or too high (≥0.5 wt.%), the stability of the prepared sunscreen composition is poor, and oiling is easy to occur in the shaker test.
[0100] 3) As shown in Table 5, when the content of the thickener polyacrylate crosspolymer-6 was fixed at 0.16 wt.%, and the content of the thickener xanthan gum was increased from 0% to 0.4 wt.%, the SPF value of the prepared sunscreen composition showed a trend of first increasing and then decreasing; the skin adhesion evaluation also showed a trend of first increasing and then decreasing and then remaining flat; when the content of the thickener xanthan gum was too low (<0.05 wt.%) or too high (≥0.4 wt.%), the stability of the prepared sunscreen composition was poor, and oiling was easily observed in the shaker test.
[0101] Commonly used thickeners in O / W sunscreen formulations include: 1) polysaccharide-based natural thickeners: xanthan gum, carrageenan; 2) synthetic thickeners: carbomers, polyvinylpyrrolidone, polyurethanes. Therefore, based on the formulation of Example 5, the content of the modified inorganic sunscreen agent was fixed at 3 wt.%, and the content of the thickener was fixed at 0.26 wt.%, resulting in Comparative Examples 13 to 17, which were then subjected to physical property and stability tests.
[0102] Comparative Example 13: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, polyacrylate crosslinking polymer-6 is not added, and the amount of xanthan gum added is adjusted to 0.26 wt.%.
[0103] Comparative Example 14: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, polyacrylate crosspolymer-6 and xanthan gum are not added, only carrageenan (the amount added is 0.26 wt.%).
[0104] Comparative Example 15: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, polyacrylate crosspolymer-6 and xanthan gum are not added, only carbomer is added (the amount added is 0.26 wt.%).
[0105] Comparative Example 16: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, polyacrylate crosspolymer-6 and xanthan gum are not added, only polyvinylpyrrolidone is added (the amount added is 0.26 wt.%).
[0106] Comparative Example 17: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that: in component B, xanthan gum is not added, and the amount of polyacrylate crosspolymer-6 is adjusted to 0.26 wt.%.
[0107] Comparative Example 18: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component B, the polyacrylate crosslinking polymer-6 is replaced with an equal amount of carbomer.
[0108] Comparative Example 19: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component B, the polyacrylate crosslinking polymer-6 is replaced with an equal amount of polyvinylpyrrolidone.
[0109] Performance Test 3: The sunscreen compositions obtained in Comparative Examples 13-17 were tested for SPF value, adhesion, and stability. The test results are shown in Table 8. Figures 4 to 8 As shown.
[0110] Table 8 Based on the above results, it can be seen that a single thickening system cannot effectively maintain the stability of the high-content powder of this invention in an O / W system, and attempts to use commonly used natural or synthetic thickeners in O / W systems still cannot achieve good stability.
[0111] Furthermore, structurally, xanthan gum, with its polyhydroxy structure, exhibits excellent water-binding capacity in aqueous solution, forming a relatively stable network structure that aids in powder dispersibility. Carrageenan, on the other hand, is a calcium, potassium, sodium, and ammonium salt of a polysaccharide sulfate ester composed of galactose and dehydrated galactose. It requires the addition of ions at high temperatures to promote micelle thickening, but a high electrolyte ion environment can cause titanium dioxide powder agglomeration. Additionally, carrageenan is not acid-resistant and should not be heated for extended periods. Based on the stability test results shown in Comparative Example 14, it can be concluded that carrageenan is unsuitable for dispersing titanium dioxide powder. From an economic perspective, xanthan gum is significantly cheaper than carrageenan. Comparing the experimental results, the sunscreen compositions prepared by the xanthan gum thickening system (Comparative Example 13) and the carrageenan thickening system (Comparative Example 14) both had relatively low viscosity. This indicates that, at the same content, natural polysaccharide thickening systems tend to form a low-viscosity state when used alone. To a certain extent, low-viscosity systems are less likely to achieve stability of high-content powders within the system. Therefore, these two thickeners are not suitable as primary thickeners to stabilize high-content composite powders. Considering the thickening mechanism, cost-effectiveness, and experimental results, xanthan gum is more suitable than carrageenan as the thickener for the high-content powder formulation of this invention.
[0112] Structurally, carbomer, polyvinylpyrrolidone, and cross-linked polyacrylate polymer-6 are all macromolecular polymers that exert their thickening effect by forming a cross-linked network structure through swelling in water. According to experimental results, the carbomer and cross-linked polyacrylate polymer-6 thickened system products (Comparative Examples 15 and 17) have higher viscosity, while the polyvinylpyrrolidone thickened system product (Comparative Example 16) has lower viscosity. To a certain extent, higher viscosity systems are more likely to achieve stability of high-content powders within the system. Therefore, in the system of this invention, carbomer and cross-linked polyacrylate polymer-6 are more suitable as thickener components to stabilize high-content powders. However, stability test results show that although the carbomer thickened system product (Comparative Example 15) has a high viscosity, the material exhibits agglomeration, which is detrimental to the consistency of the system and the uniform dispersion of the powder.
[0113] Based on the above results, in the system of the present invention, a single thickener cannot effectively stabilize high-content powders. Therefore, synergistic thickening with two thickeners is considered. Thus, based on the formulation shown in Example 5, the thickening system was adjusted according to Table 9, resulting in Comparative Examples 18 and 19 below.
[0114] Table 9 The sunscreen compositions obtained in Comparative Examples 18 and 19 were tested for SPF value, adhesion, and stability. The test results are shown in Table 10. Figures 9-10 ,Figure 32 As shown.
[0115] Table 10 From the above analysis, we can see that: 1) According to the test results shown in Table 10, when the two thickeners were used together, the samples did not show any oil at the end of the preparation process. This indicates that, compared with a single thickener, the simultaneous use of the two thickeners can exert a synergistic thickening effect and improve the stability of the system.
[0116] 2) Comparative Example 18 has a high viscosity and is accompanied by agglomeration, which is not conducive to the uniform and stable dispersion of inorganic sunscreen powder in the aqueous phase. This results in inconsistent sun protection performance of the products. According to the SPF machine test results, when the thickening system is the only variable, its sun protection ability is weak.
[0117] 3) The viscosity of Comparative Example 19 was relatively low. Compared with the single polyvinylpyrrolidone thickening system (Comparative Example 16), the viscosity increased slightly after adding xanthan gum, and the state of the sample was significantly improved immediately after preparation. However, severe oil exudation occurred after stability testing. This indicates that although the polyhydroxy structure of xanthan gum can temporarily help stabilize the aqueous powder, the overall viscosity of the system is low, and the constructed aqueous thickening system is insufficient to support the long-term stability of high-content powder.
[0118] 4) Compared with the single polyacrylate crosslinked polymer-6 (Comparative Example 17), the viscosity of Example 5 after compounding with xanthan gum was improved, and the stability test showed good performance, which was significantly improved.
[0119] 5) Comparing Comparative Examples 18, 19 and 5, it can be seen that when the thickener is the only variable, the thickening system of polyacrylate crosslinker-6 and xanthan gum exhibits better material stability and higher SPF value. It is speculated that the thickening system forms a finer aqueous network, which helps the inorganic sunscreen powder to be distributed more evenly and delicately in the aqueous phase. Compared with the powder in the agglomerated state, the powder weight is reduced, and therefore, it is easier to achieve long-term stability.
[0120] Example 10: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component D, C20-22 alcohol phosphate ester / C20-22 alcohol is replaced with an equal amount of arachidonic acid / behenol / arachidonic acid glucoside.
[0121] Example 11: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component D, C20-22 alcohol phosphate / C20-22 alcohol is replaced with an equal amount of cetearyl oleate / sorbitan oleate.
[0122] Example 12: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component D, C20-22 alcohol phosphate / C20-22 alcohol is replaced with an equal amount of cetearyl alcohol.
[0123] Comparative Example 20: This example provides a sunscreen composition and its preparation method, which is basically the same as in Example 5, except that in component D, C20-22 alcohol phosphate / C20-22 alcohol is replaced with an equal amount of PEG-100 stearate / glyceryl stearate.
[0124] Performance Test 4: The sunscreen compositions obtained in Comparative Example 20 and Examples 10-12 were tested for SPF value, adhesion, and stability. The test results are shown in Table 11. Figures 23-26 , Figure 32 As shown.
[0125] Table 11 1) According to the performance test results shown in Table 11, the appearance of the sunscreen compositions prepared by different emulsification systems was OK at the end of the preparation process, indicating that the content of emulsifier used in the test was appropriate and could meet the immediate stabilization requirements of the water and oil phases in the formulation. After the stability test, the states of Examples 10, 12, and 5 were OK, indicating that these three emulsification systems could maintain the stability of the emulsion system for a long time. However, Example 11 showed slight oil release, and Comparative Example 20 had the worst effect, showing a layered and particulate state, indicating that this emulsification system could not maintain the stability of the emulsion system for a long time. The reason for this is speculated to be that the emulsion systems used in Examples 10, 12, and 5 all contain alcohol components. In addition to connecting the water and oil phases through their own hydrophilic and lipophilic groups, they can also bond with the water phase and the hydrogenated lecithin on the surface of the modified inorganic sunscreen powder through hydrogen bonds via hydroxyl groups (-OH). Therefore, they can stabilize both the water and oil phases and the powder.
[0126] 2) Comparing the skin-adhesion and SPF values of Examples 10, 12, and 5, it is evident that Example 5 exhibits superior overall performance compared to Examples 10 and 12. The presumably, this is because, in the system of this invention, all three components in the emulsion system of Example 10 contain hydroxyl groups, especially arachidonic acid glucoside, which has a multi-hydroxyl structure. In contrast, the emulsion system of Example 12 has a single fatty alcohol structure, where some hydroxyl groups form hydrogen bonds with water molecules. During application, these hydrogen bonds break, allowing water to penetrate the skin surface more quickly. The hydroxyl groups on the surfactant then re-establish hydrogen bonds with the powder surface, causing the powder and oil to remain on the skin surface, thus reducing the product's skin-adhesion performance. The emulsion system of Example 5 is a combination of fatty acid esters and fatty alcohols, and its phosphate ester structure is similar to the phospholipid bilayer structure of cells. Therefore, it spreads more easily on the skin, resulting in higher skin-adhesion performance. Skin-adhesion performance, to a certain extent, affects the SPF value.
[0127] Example 13: This example provides a sunscreen composition and its preparation method, which is basically the same as Example 5, except that: in component D, the amount of C20-22 alcohol phosphate / C20-22 alcohol added is adjusted to 1.0 wt.%, and the amount of water added is adjusted accordingly to make the total amount 100 wt.%.
[0128] Example 14: This example provides a sunscreen composition and its preparation method, which is basically the same as Example 5, except that: in component D, the amount of C20-22 alcohol phosphate / C20-22 alcohol added is adjusted to 5.0 wt.%, and the amount of water added is adjusted accordingly to make the total amount 100 wt.%.
[0129] Comparative Example 21: This example provides a sunscreen composition and its preparation method, which is basically the same as Example 5, except that: in component D, the amount of C20-22 alcohol phosphate / C20-22 alcohol added is adjusted to 0 wt.%, and the amount of water added is adjusted accordingly to make the total amount 100 wt.
[0130] Comparative Example 22: This example provides a sunscreen composition and its preparation method, which is basically the same as Example 5, except that: in component D, the amount of C20-22 alcohol phosphate / C20-22 alcohol added is adjusted to 0.5 wt.%, and the amount of water added is adjusted accordingly to make the total amount 100 wt.
[0131] Comparative Example 23: This example provides a sunscreen composition and its preparation method, which is basically the same as Example 5, except that: in component D, the amount of C20-22 alcohol phosphate / C20-22 alcohol added is adjusted to 7.0 wt.%, and the amount of water added is adjusted accordingly to make the total amount 100 wt.%.
[0132] Performance Test 5: The sunscreen compositions obtained in Comparative Example 20 and Examples 10-12 were tested for SPF value, adhesion, and stability. The test results are shown in Table 12. Figures 27-32 As shown.
[0133] Table 12 Based on the above test results, with other factors remaining constant, increasing the content of the emulsifier C20-22 phosphate ester / C20-22 alcohol from 0 wt.% to 7.0 wt.% resulted in an initial increase followed by a decrease in the SPF value of the prepared sunscreen composition, while the skin adhesion evaluation also showed an initial increase followed by a slight decrease. Regarding stability, increasing the emulsifier content within a certain range improved the stability of the sunscreen, but when the emulsifier content was too high (≥7 wt.%), the stability of the sunscreen composition worsened. Therefore, in the system of this invention, the emulsifier content has a suitable range and a specific threshold value.
[0134] In summary, the sunscreen composition of the present invention, while possessing excellent sun protection capabilities, also exhibits good skin adhesion and formulation stability, thus improving or even overcoming the problems of current sunscreen products that struggle to balance sun protection performance with user experience and stability.
[0135] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0136] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A sunscreen composition, characterized in that, The ingredients of the sunscreen composition include: The oil phase contains at least one emulsifier; the amount of the emulsifier added is 0.8 wt.%-5.5 wt.% based on the total weight of the sunscreen composition; the emulsifier comprises one or more combinations selected from arachidonic acid / behenol / arachidonic acid glucoside, cetearyl oleate / sorbitan oleate, cetearyl alcohol, C20-22 phosphate ester / C20-22 alcohol; The sunscreen composition includes an aqueous phase containing at least a thickener; the thickener comprises at least a combination of polyacrylate crosspolymer-6 and xanthan gum, wherein the amount of xanthan gum added is 0.03 wt.%-0.25 wt.% and the amount of polyacrylate crosspolymer-6 added is 0.06 wt.%-0.35 wt.% based on the total weight of the sunscreen composition. Inorganic sunscreen agent; the amount of inorganic sunscreen agent added is 0.5 wt.%-5.0 wt.% based on the total weight of the sunscreen composition; and the inorganic sunscreen agent exists as a single phase or is pre-dispersed in the oil phase and / or the aqueous phase.
2. The sunscreen composition according to claim 1, characterized in that, Based on the total weight of the sunscreen composition, the amount of emulsifier added is 1.0 wt.%-5.0 wt.%, more preferably 2.5 wt.%-4.0 wt.%; and / or, Based on the total weight of the sunscreen composition, the amount of xanthan gum added is 0.04 wt.%-0.22 wt.%, and the amount of polyacrylate crosspolymer-6 added is 0.08 wt.%-0.32 wt.%; further, based on the total weight of the sunscreen composition, the amount of xanthan gum added is 0.05 wt.%-0.20 wt.%, and the amount of polyacrylate crosspolymer-6 added is 0.1 wt.%-0.3 wt.%; even further, based on the total weight of the sunscreen composition, the amount of xanthan gum added is 0.05 wt.%-0.15 wt.%, and the amount of polyacrylate crosspolymer-6 added is 0.1 wt.%-0.20 wt.%.
3. The sunscreen composition according to claim 1, characterized in that, Based on the total weight of the sunscreen composition, the amount of the inorganic sunscreen agent added is 2 wt.%-4 wt.%; and / or, The mass ratio of the polyacrylate crosslinked polymer-6 to the xanthan gum is 1:0.3-1.25, more preferably 1:0.35-1.0, and even more preferably 1:0.5-0.8; and / or, The mass ratio of the emulsifier, the thickener, and the inorganic sunscreen agent is 0.8-1.2:0.04-0.12:
1.
4. The sunscreen composition according to claim 1, characterized in that, The inorganic sunscreen agent is a modified inorganic sunscreen agent, which includes a core layer and a shell layer. The core layer is made of inorganic sunscreen particles, and the shell layer is made of silicon dioxide and hydrogenated lecithin. By mass percentage, the modified inorganic sunscreen agent contains 75%-88% inorganic sunscreen particles, 10%-20% silica, and 0.01%-10% hydrogenated lecithin.
5. The sunscreen composition according to claim 4, characterized in that, By mass percentage, the modified inorganic sunscreen agent contains 80%-86% inorganic sunscreen particles, 12%-18% silica, and 0.5%-4% hydrogenated lecithin; and / or, the inorganic sunscreen particles contain titanium dioxide.
6. The sunscreen composition according to claim 4, characterized in that, The modified inorganic sunscreen agent is prepared by the following method: (1) An aqueous solution of inorganic sunscreen particles was used as the substrate solution; (2) Under heating and stirring conditions, an aqueous solution of acid is added to the substrate solution to control the pH of the system to 3-5. Then, under heating and stirring conditions, an aqueous solution of sodium silicate and an aqueous solution of acid are added and the reaction is controlled at pH 3-4. After the reaction, the reaction mixture is obtained, separated, and inorganic sunscreen particles coated with silica are obtained. (3) The silica-coated inorganic sunscreen particles are activated under heating conditions and then mixed with hydrogenated lecithin.
7. The sunscreen composition according to claim 6, characterized in that, In the preparation process, the inorganic sunscreen particles in aqueous solution are first mechanically ground and ultrasonically dispersed, followed by heating; and / or, The preparation method of the modified inorganic sunscreen agent further includes a pretreatment step set between step (2) and step (1), the pretreatment step including: adding an aqueous solution of sodium silicate and an aqueous solution of acid to the substrate solution under heating and stirring conditions, reacting under conditions where the pH of the system is controlled at 8-9, and obtaining a pretreated reaction mixture after the reaction; and / or, During the preparation process, the silica content in the sodium silicate aqueous solution is controlled to be 40-60 g / L; and / or, Aqueous solutions of acids include one or more combinations of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid; and / or, In obtaining the reaction mixture, the heating conditions are controlled to maintain a system temperature of 50-60°C; and / or, The activation is controlled to be carried out at 75-90°C, and further at 80-85°C; and / or, Controlled mixing of activated silica-coated inorganic sunscreen particles with hydrogenated lecithin at 75-90°C; and / or, The mass of sodium silicate added is based on the amount of silica, and in obtaining the reaction mixture, the mass of silica added is 10%-40% of the mass of the inorganic sunscreen particles fed into the reactor; and / or, The addition of hydrogenated lecithin is based on a concentration of 0.01%-10% of the modified inorganic sunscreen agent; and / or, After adding hydrogenated lecithin and mixing, continue heat treatment at 75-90℃, and then pulverize.
8. The sunscreen composition according to claim 1, characterized in that, The oil phase also contains an oil-soluble sunscreen ingredient, which includes one or more combinations selected from homosalate, octocrylene, ethylhexyl salicylate, ethylhexyl methoxyate, and diethylamino hydroxybenzoyl hexyl benzoate. Further, based on the total weight of the sunscreen composition, the amount of homosalate added is 1 wt.%-5 wt.%, the amount of octocrylene added is 0.5 wt.%-4.5 wt.%, the amount of ethylhexyl salicylate added is 2.5 wt.%-6.5 wt.%, the amount of ethylhexyl methoxyate added is 4.5 wt.%-9.0 wt.%, and the amount of diethylamino hydroxybenzoyl hexyl benzoate added is 1 wt.%-5 wt.%. And / or, The aqueous phase further comprises polyols and skin feel modifiers; furthermore, based on the total weight of the sunscreen composition, the amount of polyol added is 5 wt.%-15 wt.%, and the amount of skin feel modifier added is 0.5 wt.%-3 wt.%. And / or, The raw materials of the sunscreen composition also include preservatives, and further, based on the total weight of the sunscreen composition, the amount of preservatives added is 0.1 wt.%-3 wt.%.
9. A method for preparing a sunscreen composition according to any one of claims 1-8, characterized in that, The preparation method includes: The components of the aqueous phase are mixed to form an aqueous phase; The components of the oil phase are mixed to form the oil phase; The oil phase is added to the aqueous phase and emulsified. Then, the inorganic sunscreen agent is added and dispersed and mixed.
10. A sunscreen product, characterized in that, The sunscreen product comprises the sunscreen composition according to any one of claims 1-8.
